Why Magnus expansion. Issue 1 (2nd January 2022) - Oteo, J. A.; Ros, J.
Abstract : A short story about the origins of Magnus Expansion, why we got involved and how it led us to meet Geometric Integration. We present a biographical draft of Wilhelm Magnus, a sketchy discussion of what is the expansion which carries his name and a derivation of the formalism equations. We explain the important feature that makes the expansion an appropriate tool to develop Geometric Integration schemes.